2011
DOI: 10.1103/physreve.84.021919
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological model of interstitial fluid pressure in a solid tumor

Abstract: Tumor interstitial fluid pressure (TIFP) has the potential to predict tumor response to nonsurgical cancer treatments, including radiation therapy. At present the only quantitative measures available are of limited use, since they are invasive and yield only point measurements. We present the mathematical framework for a quantitative, noninvasive measure of TIFP. The model describes the distribution of interstitial fluid pressure in three distinct tumor regions: vascularized tumor rim, central tumor region, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Our study was based on the hypothesis that the velocity of the fluid flow from tumors into adjacent normal tissues is determined by the IFP drop at the tumor surface. Moreover, in accordance with previous suggestions (10,(19)(20)(21), we hypothesized that the development of lymph node metastases is associated with the fluid flow out of tumors as the fluid may direct tumor-secreted lymphangiogenic factors and other metastasis-promoting chemokines toward peritumoral lymphatics. To test these hypotheses, the Gd-DTPA velocity at the tumor surface was assessed by DCE-MRI in xenografted tumors and human cervical carcinomas.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study was based on the hypothesis that the velocity of the fluid flow from tumors into adjacent normal tissues is determined by the IFP drop at the tumor surface. Moreover, in accordance with previous suggestions (10,(19)(20)(21), we hypothesized that the development of lymph node metastases is associated with the fluid flow out of tumors as the fluid may direct tumor-secreted lymphangiogenic factors and other metastasis-promoting chemokines toward peritumoral lymphatics. To test these hypotheses, the Gd-DTPA velocity at the tumor surface was assessed by DCE-MRI in xenografted tumors and human cervical carcinomas.…”
Section: Introductionsupporting
confidence: 51%
“…However, there is significant theoretical evidence that DCE-MRI parameters related to the washout of Gd-DTPA at the tumor surface may provide information on the IFP of tumors (19). This possibility was investigated in the work reported here.…”
Section: Introductionmentioning
confidence: 82%
“…where R 0 represents the boundary of the central region (an iso-pressure and iso-velocity surface), R s the tumor surface, R m the maximum position that tumor interstitial fluid can spread to, which is the location where pressure becomes the same as that in normal tissue, d 0 =R s -R 0 and d m =R m -R s (Liu and Schlesinger, 2015;Liu et al, 2011). For an isolated tumor, d m =0, so the above formula for the region R 0 <r<R s can still be applied.…”
Section: Methodsmentioning
confidence: 99%
“…TIFP may be estimated through i) approximation of the velocity of tumor exudate at tumor surface, ii) measurement of the distance from tumor surface to where the tumor exudate is absorbed (or normalized), and iii) estimation of the interstitial hydraulic conductivity, which is referred to as the K-factor of the tissue through which the tumor exudate travels (Liu and Schlesinger, 2015;Liu et al, 2011). Hompland et al (Hompland et al, 2012b) showed the method for determining the fluid velocity and size of the tumor rim based on DCE-MRI images.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, Brown, Ewing, & Schlesinger, 2011;Pusenjak & Miklavcic, 2000;Simonsen, Gaustad, Leinaas, & Rofstad, 2012). Rendering the cell membrane semipermeable in presence of pressure gradients will, in theory, result in filtration flows in the direction opposite to that of the pressure gradient both during and after electroporation.…”
Section: Accepted Manuscriptmentioning
confidence: 96%